Strengthening Democracy Through Voter Education for Generation Z: Challenges and Collaborative Solutions (JED (Jurnal Etika Demokrasi), 2025)
This article aims to describe the form of voter education for generation Z and how the related parties collaborate. This research uses a qualitative design with descriptive methods. The research was conducted in the city of Pekanbaru, specifically on Pekanbaru City KPU commissioners and election and democracy NGO activists. Research data was collected through observation, interviews, FGDs and documentation studies. The data analysis technique uses the Miles and Huberman model which consists of data collection, data verification and reduction, drawing conclusions. The triangulation technique uses data source triangulation. The results of the research found that (1) Voter education for Gen Z through several methods, namely election outreach and education for beginner voters in schools, public invitations to the Election Smart House, election podcasts, as well as via social media Instagram and  political discussions facilitated by NGOs,. ; (2) lack of cooperation between election organizers and parties related to the voter segment in conducting voter education, so that it seems partial and not comprehensive. Therefore, there needs to be a collaborative effort between election organizers, electoral NGOs and schools to strengthen generation Z's political literacy.